2016
DOI: 10.3389/fenrg.2016.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Post-Synthetic Linker Functionalization of MOFs on Methane Storage: The Role of Defects

Abstract: Natural gas is increasingly being viewed as one of the most viable alternatives to gasoline. However, its vehicular application will only be widespread if safe and high-capacity methane stores are developed. In this work, we report an over 33% increase in methane uptake on a post-synthetically modified metal-organic framework. The underlying mechanism for this dramatic increase is due to lattice defects formed upon post-synthetic modification. This method may open new approaches to natural gas storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
(67 reference statements)
0
14
0
1
Order By: Relevance
“…In 2016 Szilágyi et al reported on enhanced methane adsorption properties of postsynthetically treated MIL‐101(Cr) by 33% compared to the pristine MOF . In their work, they introduced NH 2 ‐BDC 2− (BDC 2− = 1,4‐dicarboxylate) via SALE and were able to exchange up to 20% of the original BDC 2− linkers.…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016 Szilágyi et al reported on enhanced methane adsorption properties of postsynthetically treated MIL‐101(Cr) by 33% compared to the pristine MOF . In their work, they introduced NH 2 ‐BDC 2− (BDC 2− = 1,4‐dicarboxylate) via SALE and were able to exchange up to 20% of the original BDC 2− linkers.…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…The orange polyhedra represent the cationic units, whereas C and O atoms are depicted in black and blue, respectively. Reproduced under the terms of the CC‐BY License . Copyright 2016, P. Á. Szilágyi, P. Serra‐Crespo, J. Gascon, H. Geerlings, B. Dam, Frontiers.…”
Section: Function and Properties Of Mofsmentioning
confidence: 99%
“…A segunda abordagem visa promover a funcionalização pós-sintética de MOFs com grupamentos sítio-específicos que auxiliem na adsorção do gás metano. 217,218 Uso do biogás como fonte de metano. Uma etapa crítica da utilização do biogás como combustível renovável é a sua purificação, que consiste basicamente na remoção de dióxido de carbono.…”
Section: Mofs Energia E Meio-ambienteunclassified
“…This makes MOFs very attractive materials for applications: e.g. gas storage, [2][3][4] carbon dioxide capture, [5][6][7][8] sensor applications, [9] luminescence, [10][11][12] catalysis, [13] and many more. [14][15][16][17][18] Also from the fundamental point of view, MOFs show many interesting properties.…”
Section: Introductionmentioning
confidence: 99%